Penerapan Metode Arithmetic Mean Filter Untuk Mereduksi Noise Speckle dan Salt And Paper Pada Citra Ortokromatik - Dedi Widayat; Saidi Ramadan Siregar (JURIKOM (Jurnal Riset Komputer), 2019)
Orthochromatic imagery is made using a visible spectrum from blue to partly green (0.4-0.56 micrometers). The object will appear clearer so this image is useful for coastal studies considering the film is sensitive to objects below the surface of the water to a depth of approximately 20 meters. The capture power of orthochromatic image recorder is almost the same as the sensitivity of the human eye when taking an image or image when using a camera often experiences noise in the image caused by a bad camera lens or camera position when taking an image that can cause noise in the resulting image . Noise or image greatly influences the clarity of an image where the results of the image are less clear when seen by the eye, so that noise in the image must be removed so that the image can be clearer and has a much better quality. Arithmetic Method The Mean Filter replaces the pixel value at position (x, y) with the average pixel value in the surrounding neighbor. The number of pixels about you is determined as a masking / carnel / window that is sized for example 3x3, 5x5, 10x10, and so on. Then the mean filter will be carried out for M images using the kernel matrix (5x5). Pixels also have a weighted filter approach. The ArithmeticMean Filter method for removing noise in orthochromatic images so that noise in orthochromatic images can be reduced using the Arithmetic method which has a good role in reducing speckle and salt and pepper noise.